2022
DOI: 10.1002/pen.26025
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of bottle‐grade polyethylene terephthalate: Effect of carrier gases on carriage of pyrolysis products

Abstract: The production of widely-used bottle-grade polyethylene terephthalate (PET) is now considered an environmental problem on a global scale. The urgent need for renewable energy reveals the necessity of employing thermochemical recycling methods. The use of a carrier gas is among the parameters affecting the pyrolysis process, for it is responsible for carrying pyrolysis products to separate condensable products. In this study, PET granules were pyrolyzed at 500 C with three carrier gases: N 2 , He, and Ar. Accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Since the benzoic acid and methyl radicals reacted violently, the intensity of 1,4‐dimethylbenzoate measured in the presence of argon rose nonlinearly. The argon atmosphere had the lowest biphenyl concentration, which was consistent with the clearly visible rise 29 …”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Since the benzoic acid and methyl radicals reacted violently, the intensity of 1,4‐dimethylbenzoate measured in the presence of argon rose nonlinearly. The argon atmosphere had the lowest biphenyl concentration, which was consistent with the clearly visible rise 29 …”
Section: Resultssupporting
confidence: 79%
“…This finding showed that the wax generated in the helium and nitrogen atmospheres included higher concentrations of heavy oxygenated species. With the temperature rising, they were tough to decompose and progressively polymerize 29 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Under vacuum conditions, argon is used to create the inert gas atmosphere and purge any additional contaminants in the substrate. Either hydrogen or nitrogen gases are used to react at the surface and to maintain the high temperature and pressure of the substrate. , Precursor gases such as carbon monoxide, ethane, ethylene, acetylene, benzene, and xylene mostly contain carbon sources. Methane, ethylene, and acetylene have linear dimmers of carbon atoms and they form a straight CNT, while benzene produces a curved CNT. , Acetylene has a major influence on CNT production manufactured by the CVD method.…”
Section: Introductionmentioning
confidence: 99%